2018
DOI: 10.1001/jamaneurol.2017.4011
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Rituximab and Other Initial Treatment Choices for Multiple Sclerosis

Abstract: IMPORTANCE Comparative real-world effectiveness studies of initial disease-modifying treatment (DMT) choices for relapsing-remitting multiple sclerosis (RRMS) that include rituximab are lacking. OBJECTIVE To assess the effectiveness and drug discontinuation rates of rituximab among patients with newly diagnosed RRMS compared with injectable DMTs, dimethyl fumarate, fingolimod, or natalizumab. DESIGN, SETTING, AND PATIENTS This retrospective cohort study used prospectively collected data to examine specialized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
143
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 177 publications
(157 citation statements)
references
References 30 publications
9
143
1
4
Order By: Relevance
“…However, due to the limited number of patients in the treatment groups and a high and uneven percentage of patients lacking MRI data prior to baseline, it was not considered feasible to adjust the statistical comparisons for preswitch MRI data. The results of this study, implying similar efficacy for suppression of disease activity for NTZ and RTX, are in line with a previous study on treatment-naive patients with RRMS initiating a first DMT [7]. Our results are also in line with a previous study suggesting superior efficacy of RTX compared with FGL after switch from NTZ due to JCV positivity [8].…”
Section: Discussionsupporting
confidence: 92%
“…However, due to the limited number of patients in the treatment groups and a high and uneven percentage of patients lacking MRI data prior to baseline, it was not considered feasible to adjust the statistical comparisons for preswitch MRI data. The results of this study, implying similar efficacy for suppression of disease activity for NTZ and RTX, are in line with a previous study on treatment-naive patients with RRMS initiating a first DMT [7]. Our results are also in line with a previous study suggesting superior efficacy of RTX compared with FGL after switch from NTZ due to JCV positivity [8].…”
Section: Discussionsupporting
confidence: 92%
“…4 The implementation of soluble but also novel imaging biomarkers that can complement current clinical and imaging monitoring likely will lead to an increased use of more effective DMTs and reduce the risks for patients to be exposed to insufficient treatment responses, in turn improving important long-term clinical outcomes. 12,29 We demonstrate that dynamics of pNfL are significantly influenced by specific DMTs and that the degree of pNfL reduction is correlated to clinical and patient-reported outcomes, but also that the baseline pNfL concentration exerts an unproportioned effect on on-treatment values in the medium term. In order to understand if pNfL can be used as a drug response biomarker at the individual level, further studies are needed to address the correlation of pNfL changes to long-term clinical outcomes with different DMTs, as well as if modeling of pNfL dynamics can be improved further by including additional variables such as MRI data or more frequent measurements.…”
Section: Discussionmentioning
confidence: 83%
“…Taking MS for example, monoclonal antibodies (including Rituximab and Ocrelizumab) that selectively target and deplete CD20 + B cells have been approved for the treatment of MS (Greenfield & Hauser, ; Hauser et al, ; Sabatino, Zamvil, & Hauser, ; Salzer et al, ). Our colleagues have demonstrated that relapsing–remitting MS patients with Rituximab as the initial treatment have better relapse control and tolerability in comparison with other disease‐modifying drugs (Granqvist et al, ; Spelman, Frisell, Piehl, & Hillert, ). Available MS treatments mainly resolve the peripheral inflammation but further specific and effective cell‐depletion therapies still represent a highly unmet medical need, especially in chronic disease states.…”
Section: Microglial Repopulation Resolves Neuroinflammation: New Cellmentioning
confidence: 99%